The memorable souvenir-shopping experience : antecedents and outcomes - Sthapit, Erose; Coudounaris, Dafnis; Björk, Peter (Leisure Studies, 2021)
This study examines the relationship among authenticity, satisfaction, co-creation, memorable souvenir-shopping experiences, and place attachment. A post-holiday web-based survey was conducted among tourists to Rovaniemi, Finland, and a valid sample of 301 tourists was used for data analysis. The survey results show that satisfaction and co-creation during onsite souvenir shopping at a tourism destination create memorable souvenir shopping experiences, and that such memories enhance tourists’ feelings of attachment to the destination. The implications for retail management are that souvenir vendors should offer a large assortment of souvenirs to suit tourists’ individual tastes. Souvenir retailers can enhance customer satisfaction through taking such steps as training personnel on customer shopping satisfaction, extending operating hours, broadening the accepted means of payment, and improving the quality and display of products as well as the external appearance of their shops. Additionally, souvenir retailers should interact with customers and engage in onsite co-creation to arouse interest and attention. Peer reviewed